Analisis Kualitas Makanan dan Perceived Value terhadap Kepuasan Konsumen pada Industri Rumah Makan - Clara Candra Komala; Nor Norisanti; Asep M. Ramdan (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2019)
The purpose of this study was to analysis the effect of food quality and perceived value on consumer satisfaction in the restaurant industry. The sample used in this research was 98 respondents and data collection methods using a questionnaire. The method used in this study is the use the type of probability sampling includes in the simple random sampling. The analysis technique using validity test, reliability test, multiple linear regression analysis, including test coefficient of determination, multiple correlation coefficient, and simultaneous test (F test).The results of the test coefficient of determination seen from value (Adjusted R2) of 0,473 can be interpreted that the effect of Food Quality and Perceived Value on consumer satisfaction is 4,73%. The remaining 52,7% is influenced by other factors not explained in this study. Based on the multiple correlation coefficient test seen from the R value of 0.696, it shows that there is a strong relationship between food quality and perceived value with customer satisfaction. Based on the F test the probability value sig. 0,000 <0,05, which means that together Food Quality (X1) and Perceived Value (X2) significantly influence customer satisfaction (Y).